Investment Plan and Evaluation of the Transition of a Farm to a Wellness Tourist Farm - Klakočar, Tatjana; Pažek, Karmen; Pavić, Lazar (Agricultura Scientia, 2023)
This study aimed to develop a commercial concept for transforming farms into wellness tourist destinations. The proposed scenario involved the renovation of a hayrack into a highend tourist accommodation, comprising relaxation rooms with panoramic glass walls and the renovation of the barns, as well as an outdoor swimming pond. The research methods includeddescription, compilation, and synthesis to explore the legislation in Slovenia related to investment performance and trends in wellness tourism to support the realisation of the proposed investment. Furthermore, the study used the method of financial estimation of investment using cost-benefit analysis to facilitate the transition. Four datasets were used for the estimation: investment income, investment costs, end value of the investment, and annual interest rate. The estimated investment cost was €530,000 and the total estimated revenue was €192,720, with total costs amounting to 50% of the total income, as well as an annual cash flow of €96,360, which was used in the assessment of the investment return period. According to the findings, the investment return period is 15 years with the lowest annual cash flow and interest rate of 3.5%. However, caution is advised due to uncertainties in the long-term costs of raw materials and energy.
Keywords: tourist farm; wellness; cost-benefit analysis